Aortic valve neocuspidization with autologous Pericardium using Sizers and Templates: Short-Term outcomes - Varbanets, S. V.; Gurjeva, O. S.; Kosiura, A. S.; Yemets, G. I.; Yemets, I. M. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Background. Despite certain disadvantages of aortic valve replacement (AVR) using biological prosthesis, e.g. valve degeneration and non-optimal haemodynamic properties, it’s becoming more popular in patients of different age groups. The use of autologous pericardium for aortic valve (AV) reconstruction could be a reasonable alternative to AVR and may provide slower degeneration of neo-AV due to the absence of patient-prosthesis immune reaction as well as optimization of haemodymanics resulting from preservation of normal physiology of aortic root. Objective. To study the opportunities of AV reconstruction in children and in adults with autologous tissues using different techniques and to evaluate short-term outcomes of surgical treatment. Methods. From 01/2015 to 06/2019 we have performed AV reconstruction with autologous pericardium in 50 patients with AV disease. Of these, 18% (n = 9) were children from 6 to 18 years of age. Three methods of AV reconstruction were applied: 1) AV reconstruction with solid autopericardial patch (n = 1); 2) AV reconstruction with separate autopericardial leaflets without use of sizers (n = 3); 3) AV reconstruction with separate autopericardial leaflets using sizers and templates (n = 46). Reusable resterilizable sizers and corresponding templates were constructed according to the formulas proposed by W. Gasparyan and manufactured as a sample set by Med-Service Ltd, Kyiv, Ukraine. In 39 patients (84.78%) we have used Ozaki leaflet implantation technique. Results. There were no fatal cases during the observation period. In 94% of patients (n = 47), good outcomes of AV reconstruction were observed: AV was competent in 74% (n = 37) of patients, aortic regurgitation (AR) was trivial in 12% (n = 6) of cases, and 8% (n = 4) of patients had mild AR on discharge. It should be noted that in 2 of 47 patients moderate AR was diagnosed and successfully corrected intraoperatively after reclamping of aorta. Three patients (6%) with bicuspid AV anatomy were diagnosed with moderate or severe AR which required reoperation during the same hospitalization. In one case AR was corrected by means of repeated reconstruction. In two other cases AV valve was replaced with mechanical prosthesis. Conclusions. AV neocuspidization with autologous pericardium is a safe procedure which demonstrates good short-term outcomes. The use of originally produced set of sizers and templates developed according to W. Gasparyan’s formula in combination with Ozaki technique of leaflets implantation simplify the procedure, are time-saving and improve reproduc-ibility of the operation performed.